2016
DOI: 10.1016/j.jbi.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A new algorithmic approach for the extraction of temporal associations from clinical narratives with an application to medical product safety surveillance reports

Abstract: The sheer volume of textual information that needs to be reviewed and analyzed in many clinical settings requires the automated retrieval of key clinical and temporal information. The existing natural language processing systems are often challenged by the low quality of clinical texts and do not demonstrate the required performance. In this study, we focus on medical product safety report narratives and investigate the association of the clinical events with appropriate time information. We developed a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…MedEx was previously found to perform well at identifying drug names and dose-related information, such as strength, route, and frequency [8,16,17]. ETHER's text mining capabilities have been extensively evaluated as well with a demonstrated efficiency in the extraction of drug names and temporal information [10,18]. The NLP output was subsequently analyzed in PANACEA, a NA tool that supports the analysis of complex relationships in large datasets over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MedEx was previously found to perform well at identifying drug names and dose-related information, such as strength, route, and frequency [8,16,17]. ETHER's text mining capabilities have been extensively evaluated as well with a demonstrated efficiency in the extraction of drug names and temporal information [10,18]. The NLP output was subsequently analyzed in PANACEA, a NA tool that supports the analysis of complex relationships in large datasets over time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the reviewers concluded that no TSD should have been assigned by ETHER to many of the drug mentions. However, this should not characterize ETHER's ability to support this task as it is related to its particular configuration: if a drug is not directly linked to an absolute time statement in the text, ETHER will (and has been set to) assign an exposure date according to either the submission date or other time information in the narrative [10]. ETHER's configuration to avoid missing values can be easily changed to accommodate the requirements in other tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When applied to the TempEval-2 newspaper data, both systems achieved stateof-the-art performance (F1 scores of 92% and 86%, respectively, for time expression identification) (Verhagen et al, 2010). Moreover, they have previously been used for the automatic processing of clinical narratives (Jindal and Roth, 2013;Wang et al, 2016).…”
Section: Automated Time Expression Extractionmentioning
confidence: 99%
“…The current natural language processing systems are often hampered by low quality text (e.g., poor grammar, many abbreviations). CBER developed an algorithm for analyzing low quality texts that is minimally dependent on grammatical and syntactic information (30). This will speed reviewer extraction and analysis of important information, and accelerate recommendations about post-marketing adverse events related to medical product use.…”
Section: Improving Clinical Evaluation Pre- and Post-licensure Througmentioning
confidence: 99%